2006
DOI: 10.1007/s00232-006-0875-7
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of Cationic Amino Acid Transporters (CATs)

Abstract: The CAT proteins (CAT for cationic amino acid transporter) are amongst the first mammalian amino acid transporters identified on the molecular level and seem to be the major entry path for cationic amino acids in most cells. However, CAT proteins mediate also efflux of their substrates and thus may also deplete cells from cationic amino acids under certain circumstances. The CAT proteins form a subfamily of the solute carrier family 7 (SLC7) that consists of four confirmed transport proteins for cationic amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
193
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(198 citation statements)
references
References 95 publications
3
193
1
1
Order By: Relevance
“…It is suggested that L-ornithine uptake via CAT1 plays a crucial role in ornithine cytotoxicity in hTERT-RPE cells (Kaneko et al 2007a). On the other hand, CAT1 functions as an amino acid exchanger and has been suggested to work as an efflux transporter of L-ornithine in cells with a high intracellular concentration of L-ornithine (Closs et al 2006). Therefore, it is speculated that CAT1 at the inner BRB also plays an important role in the pathogenic changes in gyrate atrophy of the choroids and retina, although further studies are needed to elucidate whether it is beneficial or detrimental.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that L-ornithine uptake via CAT1 plays a crucial role in ornithine cytotoxicity in hTERT-RPE cells (Kaneko et al 2007a). On the other hand, CAT1 functions as an amino acid exchanger and has been suggested to work as an efflux transporter of L-ornithine in cells with a high intracellular concentration of L-ornithine (Closs et al 2006). Therefore, it is speculated that CAT1 at the inner BRB also plays an important role in the pathogenic changes in gyrate atrophy of the choroids and retina, although further studies are needed to elucidate whether it is beneficial or detrimental.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the four genes may be expressed with higher levels on E9 or E11. It is well known that CAT proteins transport cationic amino acids in a Na + -independent way (Closs et al, 2006). However, the system y + cationic amino acid transport (CAT) family undergoes adaptive upregulation during amino acid starvation (Humphrey et al, 2006) and thus might be repressed by nutrient provision from the yolk stalk.…”
Section: Gene Expressionmentioning
confidence: 99%
“…For flow cytometry, Abs against human CD2 (6F10.3), CD14 (RM052), CD19 (J4.119), CD80 (MAB104), CD83 (HB15A) (all Beckmann Coulter, Krefeld, Germany), CD86 (BU63, Serotec, Oxford, U.K.), HLA-DR (YD1/ 63.4.10, Serotec), nNOS (nNOS-AB, A-11, Santa Cruz Biotechnology, Santa Cruz, CA), CD40 (5c3), CD208-APC (110-1112) (all Becton Dickinson), CCR7-APC (150503; R&D Systems, Wiesbaden, Germany), mouse (MOPC-31-C, MOPC-173, [27][28][29][30][31][32][33][34][35], and rat (R35-95, MOPC-21) subclassspecific isotypes (all Beckmann Coulter) were used. Conjugated secondary reagents: FITC-conjugated goat-anti-rat-IgG (Biozol, Eching, Germany), PE-conjugated donkey anti-mouse-IgG (Jackson ImmunoResearch Laboratories, Suffolk, U.K.), for myeloid DC: anti-CD1c-PE (M241, Ancell, Cologne, Germany).…”
Section: Absmentioning
confidence: 99%
“…Arginine is provided to cells by specific carrier proteins. Among these, the so called cationic amino acid transporters (CATs) are considered to be the major route of uptake in most cells and tissues (29,30). Individual CAT isoforms have been postulated to be important for the substrate supply of the different NOS isoforms: CAT-1 for eNOS, CAT-2B for iNOS, and CAT-3 for nNOS.…”
Section: Unaltered Expression Of Arginase and Cationic Amino Acid Tramentioning
confidence: 99%